Unveiling Gender Dynamics: An In-depth Analysis of Gender Realities - Fernandez, Luiz (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This journal article presents a comprehensive exploration of gender dynamics through an in-depth analysis of gender realities. By delving into the intricate interplay of cultural norms, evolving identities, educational empowerment, and gender-based discrimination, this study sheds light on the complexities shaping gender experiences. The research employs qualitative methods, including semi-structured interviews and thematic analysis, to capture diverse perspectives across India. The findings reveal a nuanced spectrum of gender dynamics, emphasizing the intersectionality of identity, the evolving definitions of masculinity and femininity, and the impact of educational opportunities. The study underscores the challenges posed by gender-based discrimination and violence, while also highlighting the potential for progress through policy interventions and societal shifts. Overall, this research contributes to a deeper understanding of the intricate fabric of gender dynamics, urging for concerted efforts towards fostering gender equality and social justice.